Diseño de una plataforma mecánica rodante con capacidad de carga de 900 kg que sustituya temporalmente las funciones de un neumático averiado, utilizando el método de optimización topológica (2020)
This work presents the development of the design of a product that gives a prompt and temporary solution to the possible mishaps that may arise on the road due to the occasional failure of a tire. The design of this device has the function of supporting the load exerted by the vehicle on one of its wheels and replacing its functions to guarantee the integrity of the user and the vehicle. For this, it was defined as an initial parameter that the product will support a maximum static load of 900 kg (8829 N) and that it will obtain a mass of less than 20 kg but that it will continue to maintain its rigidity. Topological optimization corresponded to the method that was used to fulfill this requirement. This study was systematically integrated into the design methodology, starting from the collection and analysis of the products already on the market to generate a series of concepts that were evaluated from their technical characteristics up to the synthesis of the mechanical design of the platform components. With the implementation of this method, a reduction in mass and volume of 47% and 46% respectively was achieved. And the finite element analyzes validated the stiffness conservation of the component. The final result presents a design with variations in its functions in terms of the direction and weight of the device, superior to those of the products that are on the market, in addition, it satisfies each of the stated objectives.